Cost-effectiveness and economies of scale of a mass radio campaign to promote household life-saving practices in Burkina Faso. Issue 4 (16th July 2018) - Kasteng, Frida; Murray, Joanna; Cousens, Simon; Sarrassat, Sophie; Steel, Jennifer; Meda, Nicolas; Ouedraogo, Moctar; Head, Roy; Borghi, Josephine
Abstract : Introduction: Child health promotion through mass media has not been rigorously evaluated for cost-effectiveness in low-income and middle-income countries. We assessed the cost-effectiveness of a mass radio campaign on health-seeking behaviours for child survival within a trial in Burkina Faso and at national scale. Methods: We collected provider cost data prospectively alongside a 35-month cluster randomised trial in rural Burkina Faso in 2012–2015. Out-of-pocket costs of care-seeking were estimated through a household survey. We modelled intervention effects on child survival based on increased care-seeking and estimated the intervention's incremental cost-effectiveness ratio (ICER) in terms of the cost per disability-adjusted life year (DALY) averted versus current practice. Model uncertainty was gauged using one-way and probabilistic sensitivity analyses. We projected the ICER of national-scale implementation in five sub-Saharan countries with differing media structures. All costs are in 2015 USD. Results: The provider cost of the campaign was 7 749 128 (9 146 101 including household costs). The campaign broadcast radio spots 74 480 times and 4610 2-hour shows through seven local radio stations, reaching approximately 2.4 million people including 620 000 direct beneficiaries (pregnant women and children under five). It resulted in an average estimated 24% increase in care-seeking for children under five and a 7% reduction in child mortality per year. The ICER was estimated at 94 (111 including household costs (95% CI −38 to 320)). The projected provider cost per DALY averted of a national level campaign in Burkina Faso, Burundi, Malawi, Mozambique and Niger in 2018–2020, varied between 7 in Malawi to 27 in Burundi. Conclusion: This study suggests that mass-media campaigns can be very cost-effective in improving child survival in areas with high media penetration and can potentially benefit from considerable economies of scale. Trial registration number: NCT01517230 ; Results.